PENERAPAN STRATEGI PEMBELAJARAN KOOPERATIF "MAKE A MATCH" UNTUK MENINGKATKAN HASIL BELAJAR - Wawan Gunawan (Asaatidzah, 2023)
This research is to answer the problem formulation "Can the application of the "make a match" cooperative learning strategy improve Islamic Religious Education learning outcomes regarding Faith in the Books of Allah. This research uses a qualitative approach with the type of Classroom Action Research (PTK). The research subjects were class IV students at SDN Kebon Baru IV Cirebon City 2022/2023. The data collection technique used in this research is (1) participant observation method because the teacher as a researcher simultaneously observes and is observed directly by collaborators who also observe the activity of teachers and students during the learning process. (2) documentation method, used to determine students' initial abilities and to obtain data about SDN KebonBaru IV Cirebon City 2022/2023 which includes the school profile and its vision and mission, (3) test method is used to determine student learning outcomes after working on the questions questions given at the end of learning in each cycle. The data in this research is divided into two types, namely quantitative data and qualitative data. The research was carried out in four stages. The first stage is pre-cycle using the lecture method with an average score of 53 from the Minimum Completeness Criteria (KKM) 60 with student completeness of 49.6%. The second stage, cycle I, resulted in an average class score of 71 achieved by 9 students who completed it out of 12 students, with a completeness level reaching 75%. The third stage of cycle II with an average class score of 82 achieved by 12 students completed it with 100% completeness. And the fourth stage of cycle III with an average class score of 84 achieved 100% completion by 12 out of 12 students. Based on this data, by implementing the cooperative learning strategy "make a match", cycles I, II and III can be seen that there is an increase in learning outcomes after implementing the "make a match" learning strategy.